Gain enhancement for circularly polarized double layered printed hemispherical helical antenna arrays - Latef, T.A.; Khamas, S.; Reza, A.W. (2015)
To improve the performance of mobile satellite communications, such as for INMARSAT-M mobile vehicles, antenna with high gain and circular polarization over a wide angular range is important. With only 3-elements circularly polarized double-layered printed hemispherical helical antenna arrays that incorporated with parasitic helical wire in the structure, the array can produce significant improvement where it has been demonstrated that the gain and the 3dB axial ratio (AR) bandwidth and beam width can be increased by properly adjusting the relative angular displacement (1), (2), (3), and the inter-element spacing d(x) and d(y). Experimental and theoretical results demonstrate that the array can produce a gain of 11dBi, the 3dB AR bandwidth of more than 11 with AR beam width of similar to 136 degrees, and the mutual couplings between each element less than -23dB at required 3dB AR bandwidth frequency range. The antenna design is performed in computer simulation technology and verified by measurement.